A Culture-Based Strategy Is More Cost Effective Than an Empiric Therapy Strategy in Managing Pediatric Helicobacter pylori Infection - Hung, Chi-Wen; Chen, Solomon Chih-Chen; Ku, Li-Jung Elizabeth; Sheu, Bor-Shyang; Yang, Yao-Jong (Frontiers in Pediatrics, 2022)
Background: Helicobacter pylori infection is a major cause of peptic ulcers and gastric cancer. This study aimed to compare the eradication rate and essential costs of culture-based and empiric therapy strategies in treating pediatric H. pylori infection. Methods: We retrospectively enrolled patients aged less than 18 years with a diagnosis of H. pylori infection who received esophagogastroduodenoscopy at two medical centers in southern Taiwan from 1998 to 2018. Patients with positive cultures and minimum inhibitory concentration test results were allocated to a culture-based strategy, and those with negative cultures or without culture as an empiric therapy strategy. We collected demographic data and eradication rates, and calculated the total essential costs of treating a hypothetical cohort of 1,000 pediatric patients based on the two strategies. Results: Ninety-six patients were enrolled, of whom 55 received a culture-based strategy and 41 received an empiric therapy strategy. The eradication rates with the first treatment were 89.1% and 75.6% in the culture-based and empiric therapy strategy, respectively. There were no significant differences in age, sex, and endoscopic diagnosis between the two strategies. For every 10% increase in those receiving a culture-based strategy, the total cost would have been reduced by US$466 in a hypothetical cohort of 1,000 patients. For every 10% increase in successful eradication rate, the total cost was reduced by US$24,058 with a culture-based strategy and by US$20,241 with an empiric therapy strategy. Conclusions: A culture-based strategy was more cost effective than an empiric therapy strategy in treating pediatric H. pylori-infected patients.